Implementasi Pendidikan Karakter Melalui Kantin Kejujuran di Pondok Pesantren Al-Ilahiyyah Payak I Rejoagung Ngoro Jombang - Mujahidin Mujahidin; Nunung Nurjanah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2022)
This study aims to describe the implementation of character education through the Honesty Canteen at the Al-Ilahiyyah Islamic Boarding School Payak I Rejoagung Ngoro Jombang. Researchers use the type of field research (field research) with a qualitative approach to data collection using interviews, documentation and observation. The results of this study are 1. The application of the character of students is obedient to the caregiver, polite, diligent in worship and work, active, maintaining cleanliness, honest and responsible. 2. Implementation of honesty canteen in shaping the character of students through honesty canteen, namely students buying food and drinks in the canteen honestly. 3. Supporting and inhibiting factors for implementing honesty canteens in shaping the character of students, namely: through internal factors of conscience, desire or strong will, good habits by implementing honesty canteens and external factors including environmental and family influences. So it can be concluded that: 1. Application the character of the santri in the Al-Ilahiyyah Payak I Islamic boarding school Rejoagung Ngoro Jombang according to the scope and values ??of character education in an Islamic perspective reflects the good character of the santri.2. the implementation of the honesty canteen in shaping the character of students at the Al-Ilahiyyah Payak I Islamic boarding school Rejoagung Ngoro Jombang through three important theories regarding the purpose of studying morality so that it will improve attitudes and daily behavior. 3. The supporting and inhibiting factors for the implementation of the honesty canteen in shaping the character of the students are divided into two factors, namely internal and external.